Systemic Comorbidity in Children with Cataracts in Nigeria: Advocacy for Rubella Immunization - Roseline Duke; Sidney Oparah; Adedayo Adio; Okon Eyo; Friday Odey (Journal of Ophthalmology)
Background. Congenital and developmental cataracts are leading causes of childhood blindness and severe visual impairment. They may be associated with systemic diseases including congenital heart diseases which are among the major causes of morbidity and mortality in childhood. The pattern of systemic comorbidities seen in children diagnosed with cataract in Calabar, Nigeria, was studied. Methods. A retrospective review was conducted on the children who had cataract surgery between 2011 and 2012. Diagnosis of the systemic condition was documented. Results. A total of 66 children were recruited for the study. Cardiac disease was seen in 26 children (39.9%), followed by delayed milestone in 16 (24.2%), intellectual disability in 14 (21.2%), deafness in 11 (16.7%), epilepsy in 4 (6.1%), and physical handicap in 3 (4.5%) of them. Clinically confirmed Congenital Rubella Syndrome was seen in 30 (45%) of the children. The pattern of CHD seen was as follows: patent ductus arteriosus in 16 (24.2%) followed by ventricular-septal defect in 5 (7.6%), atrial-septal defect in 3 (4.5%), and pulmonary stenosis in 2 (3%). Conclusion. Systemic comorbidities, especially cardiac anomalies, are common among children with cataract in Nigeria. Congenital Rubella Syndrome may be a prominent cause of childhood cataract in our environment. Routine immunization of school girls against rubella is advocated as a measure to mitigate this trend.